The Potential Therapeutic Role of Proton Pump Inhibitors in COVID-19: Hypotheses Based on Existing Evidences - Ray, Avik; Sharma, Swati; Sadasivam, Balakrishnan (Drug Research, 2020)
Although the major therapeutic uses of the proton pump inhibitors are in gastric-acid related diseases, evidences are suggestive of a pleiotropic nature of the compounds. We comment on the probable pathways and cellular machineries via which proton pump inhibitors could show beneficial therapeutic effects against SARS-CoV-2 based on the existing evidences. Proton pump inhibitors have shown antiviral potencies in various in vivo and in vitro studies. Some of the major possible ways through which they can act against SARS-CoV-2 are by exerting anti-inflammatory and anti-fibrotic effects, via vacuolar ATPase pumps leading to raised endolysosomal pH and by targeting endosomal complexes. The current pandemic has put forward a challenge to find treatment options. Although the potential roles of proton pump inhibitors against SARS-CoV-2 have been discussed in recent publications, the clinical evidences for their real-world effectiveness do not point towards a beneficial effect clearly yet. We suggest that although proton pump inhibitors should strongly be considered as potential therapeutic options for COVID-19, larger studies in the form of randomized controlled trials would be required to arrive at a definite conclusion.
Keywords: pharmacology; molecular pharmacology; infectious diseases; gastrointestinal pharmacology; antiviral drugs